The future of nurse education in Australia and implications for perioperative nursing - Jed Duff (Journal of Perioperative Nursing)
Recently there has been a national review into nurse education in Australia conducted by Emeritus Professor Steven Schwartz on behalf of the federal government. The aim was to examine the current educational preparation of Australian nurses to ensure the profession is adequately equipped to meet the future needs of the nation’s evolving health system. The review was shaped by extensive consultations across Australia, with more than 1100 educators, clinicians, supervisors, policymakers, patient groups, students, managers and unions providing feedback. I think it is appropriate to review the report here because of the importance, as ACORN stated in its most recent strategic plan, of influencing the nursing curriculum to ensure a greater focus on perioperative care. Below, I outline some of the key recommendations from the report and their potential implications for perioperative nursing.